Public selves of adolescents as presented through the use of self-presentational strategies in different contexts - Acosta, Ronabelle Corpuz; Cruz, Vannilyn de Vera (2007)
This academic output took its ground in discussing the public selves of adolescents as presented through the five defined self-presentational strategies(SPS) as adapted by the researchers from Jones and Pittman. These self-presentation strategies are ingratiation, competence, intimidation, supplication and exemplification. This education task also took steps in finding out whether context, gender and the interaction of gender and context would influence adolescents in choosing a particular SPS. The Dependent Variables(DVs) in this research are the five SPS and the Independent Variables(IVs) here are the five defined context namely family, friends, enemies, partner in a romantic relationship and strangers. Gender, in this study takes its role as a Moderator Variable(MV). This research takes its theoretical foundation from Erving Goffman with regard to his ideas on dramaturgical analysis which implies the ideas that social actors are like stage actors who would perform in pleasing and appealing manner to his or her audiences. The respondents of this study are 160 male and 160 female high school students from the science curriculum at Baguio City National High School-Main. Those students of the said institution were evenly and randomly selected from first year to fourth year. To be specific a systematic random sampling was carried out in the selection and in the assignment of the participants in this study to the conditions pr the context defined. Results of this academic endeavor were obtained by utilizing several statistical tools. These include Uni-variate Factorial Analysis specially Test of Between-Subjects Effects (which aims to identify whether there are significant interactions between the IVs, DVs, MV),Turkey HSD test(to identify what are the context to which SPS were most used) and Descriptive Statistics (for the researchers to determine what was the most and the least preferred SPS of adolescents across contexts.)From these statistical procedures the researchers were able to obtain several findings. The study yielded results that intimidation appeared to be the most used SPS by adolescents when they are dealing with their family, friends and partner in a romantic relationship. On the other hand, the strategy competence was known to be the most used tactic when they are confronted with their enemies. Furthermore, when adolescents are interacting with strangers, supplication is mostly employed. In line with this research showed that contexts of adolescents could greatly account for their preference of using specific SPS. From this study it could also be derived that adolescents preference in using SPS as affected by gender could only be observed with the technique of competence and intimidation. Lastly, this academic task figured out that interaction of gender and context only exist when adolescents were choosing the SPS known as ingratiation -- Authors abstract.